2017
DOI: 10.1148/radiol.2017162385
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Measurements of Altered Placental Oxygenation in Pregnancies Complicated by Fetal Growth Restriction

Abstract: Purpose To evaluate oxygen-enhanced and blood oxygen level-dependent (BOLD) magnetic resonance (MR) imaging parameters in normal pregnancies and those complicated by fetal growth restriction (FGR). Materials and Methods This case-control study was approved by the local research ethics committee. Informed consent was obtained from all subjects. From October 2010 to October 2015, 28 women with uncomplicated pregnancies (individualized birthweight ratio [IBR] >20th percentile and delivery >37 weeks) and 23 with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
90
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 23 publications
5
90
1
Order By: Relevance
“…The largest studies found a strong negative correlation between baseline T2* and gestational age ,21,25,27 , while Ingram et al . found a non‐significant negative correlation and a small study on 14 pregnant women failed to demonstrate any correlation with gestational age.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The largest studies found a strong negative correlation between baseline T2* and gestational age ,21,25,27 , while Ingram et al . found a non‐significant negative correlation and a small study on 14 pregnant women failed to demonstrate any correlation with gestational age.…”
Section: Introductionmentioning
confidence: 87%
“…The main purpose of these studies was to estimate the baseline T2* value in normal pregnancy and in pregnancy complicated by FGR. In addition, the hyperoxic placental T2* response (ΔT2*) has been addressed in five of these studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations